Conflict Resolution in Aceh: A Sociological Study of Ecological Sustainability and Palm Oil - Zainal, Suadi; Ilham, Iromi; Fakhrurrazi, Fakhrurrazi; Arifin, Awaludin; Aulia, Faizul (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2024)
This article aims to explain the complexity of the realities surrounding the resolution of the conflict that occurred in Aceh, Indonesia related to the transformation of the Aceh Darul Islam movement and ecological sustainability in the development of oil palm in Aceh Tamiang Regency. This resolution in the form of oil palm development in Aceh Tamiang was carried out as empowerment of former DI/TII troops to reduce the occurrence of armed conflict in Aceh. On the other hand, the existence of palm oil plantations of former DI/TII troops in Aceh Tamiang raises concern about the reality of the impact of ecological sustainability. This study was carried out using qualitative methods, analyzed using sociological law theory. Data was collected by means of interviews and documentation studies.The results showed that The conflict transformation of the Aceh Darul Islam movement focused on the reintegration of ex-combatants into civil society with an emphasis on social, economic, and political aspects. This process involved economic empowerment, particularly through the oil palm plantation programme, to achieve peace and improve welfare in Aceh. The central government engaged in diplomacy with former DI/TII elites, integrating them in the development of oil palm plantations to maintain stability. Furthermore, it can be asserted that in the perspective of law sociology, the transformation of conflict resolution is the presence of the state that is able to create peace and social harmonisation through ecological sustainability with the release of green land and environmental management. Overall, conflict resolution efforts in the form of economic empowerment, environmental preservation and social order are key elements in building peace and sustainability in Aceh.